Hubungan Derajat Nyeri pada Brief Pain Inventory dengan Stadium Kanker Payudara - Siregar, Muthiah Alfiah Anggi; Fadinie, Wulan (Jurnal Kesehatan Andalas, 2022)
Breast cancer is a condition in which cells have undergone normal repairs, resulting in abnormal growth. In Indonesia, patients with metastatic cancer (stage IV) tend to have a lot of complaints and complications due to cancer they experience. Pain is the main complaint that is often complained of. Objectives: To determined the relationship between the degree of pain in BPI (Brief Pain Inventory) and the stage of breast cancer. Methods: Â Research conducted is analytic with cross-sectional design. The study sample was patients diagnosed with breast cancer in RSUP HAM who had met the inclusion and exclusion criteria based on the total sampling method. Research data are primary data taken using interview techniques. The research instrument was the BPI questionnaire. BPI is a measure of pain experience that measures the severity of pain and disruption of daily functioning due to the pain experienced by patients. Measured using a ratio scale where the score of 0 is the lowest and the ten highest scores have the worst pain intensity. Results: The analysis of the Chi-square test showed a significant relationship between the degree of pain and the stage of breast cancer in RSUP HAM with a p= 0,01 (p<0,05. Conclusion: There is a relationship between the degree of pain and the stage of breast cancer.Keywords: Â BPI, breast cancer, pain, stage